Significant changes in hepatic transcriptome and circulating miRNAs are associated with diet‐induced metabolic syndrome in apoE3L.CETP mice. Issue 11 (23rd April 2019) - Nasias, Dimitris; Evangelakos, Ioannis; Nidris, Vasilis; Vassou, Despoina; Tarasco, Erika; Lutz, Thomas A.; Kardassis, Dimitris
Abstract: Long‐term exposure to excess dietary fat leads to obesity and the metabolic syndrome (MetS). The purpose of the present study was to identify global changes in liver gene expression and circulating miRNAs in a humanized mouse model of diet‐induced MetS. Male apoE3L.CETP mice received a high‐fat diet (HFD) or a low‐fat diet (LFD) for different time periods and the progression of MetS pathology was monitored. A separate group of mice was divided into responders (R) or nonresponders (NR) and received HFD for 16 weeks. We found that mice receiving the HFD developed manifestations of MetS and displayed an increasing number of differentially expressed transcripts at 4, 8, and 12 weeks compared with mice receiving the LFD. Significantly changed genes were functionally annotated to metabolic diseases and pathway analysis revealed the downregulation of genes in cholesterol and fatty acid biosynthesis and upregulation of genes related to lipid droplet formation, which was in line with the development of hepatic steatosis. In the serum of the apoE3L.CETP mice we identified three miRNAs that were upregulated specifically in the HFD group. We found that responder mice have a distinct gene signature that differentiates them from nonresponders. Comparison of the two diet intervention studies revealed a limited number of common differentially expressed genes but the expression of these common genes was affected in a similar way in both studies. In conclusion, the characteristic hepatic gene signatures and serum miRNAs identified in the present study provide novel insights to MetS pathology and could be exploited for diagnostic or therapeutic purposes. Abstract : ApoE3L.CETP mice receiving a high‐fat diet (HFD) developed manifestations of metabolic syndrome (MetS) and displayed an increasing number of differentially expressed transcripts at 4, 8, and 12 weeks compared with mice receiving a LFD. We identified three miRNAs that were upregulated specifically in the serum of the apoE3L.CETP mice receiving the HFD. Responder (R) mice have a distinct gene signature that differentiates them from nonresponders (NRs).